Analysis of Students’ Extrinsic Motivation of Information Overload in English Language Learning - Efa Fitriani (Journal of Linguistics and Language Teaching, 2026)
Advancements in digital technology have made it easier for students to access various English learning resources. However, this ease of access also increases the risk of information overload—a condition where the volume of information received exceeds an individual's capacity to process it effectively. This condition has the potential to influence students' extrinsic motivation during the learning process. This study aims to analyze the impact of information overload on students' extrinsic motivation in English learning using a literature review approach. A qualitative descriptive literature review method was employed. Data were gathered from ten scholarly articles published between 2018 and 2025, selected based on their relevance to the topics of information overload, extrinsic motivation, digital technology, and English learning. The data were analyzed using content analysis techniques, involving identification, selection, thematic categorization, and the synthesis of research findings. The results indicate that the development of digital technology has a dual impact on students' extrinsic motivation. On one hand, easy access to diverse learning resources boosts students' motivation to achieve academic goals, such as obtaining good grades, meeting assignment requirements, and improving English proficiency. On the other hand, excessive exposure to information leads to confusion in selecting learning resources, increases cognitive load, reduces study focus, and potentially diminishes extrinsic motivation. The study concludes that digital literacy skills, information management, and the wise use of technology are crucial factors in minimizing the impact of information overload, thereby enabling a more effective English learning process.